Syariah dan Relasinya Islamic Human Resource Development (I-HRD) di Universitas dengan Asas Worldview Ekonomi Islam - Rakhmad Agung Hidayatullah; Muhammad Kholid Muslih; Amir Reza Kusuma; Muhammad Dhiaul Fikri (Jurnal Ilmiah Ekonomi Islam, 2023)
In the context of Islamic higher education, human resource development is also key to the implementation of teaching, learning and overall active relationships. IHRD is closely related to sharia. Each law has its own main object. The main object of Islamic sharia in general is to create benefits for mankind. Usury is forbidden to safeguard the interests of the weak and poor from exploitation by the capitalists.. Studies on the existence of IHRD in universities, educational institutions and many human empowerment institutions are carried out massively for the sustainability of the education system in the future. Therefore, in building IHRD with the foundation of the Islamic worldview, it is necessary to practice what is used as a form of employee development with a process that runs continuously. New problems, new procedures, new equipment, new restraints and new positions always arise in a dynamic organization, as for the steps that can be taken to create a higher education IHRD by means of mental, spiritual, educational and teaching worldview Islamic education and providing economic knowledge based on the Quran and Sunnah.